CircNUP98 Suppresses the Maturation of miR-519a-3p in Glioblastoma - Lu, Jun; Lou, Gaojie; Jiang, Lin; Liu, Xiaoxing; Jiang, Jianxin; Wang, Xiaolin (Frontiers in Neurology, 2021)
Although circNUP98 has been reported to promote renal cancer, its participation in other cancers is unknown. The involvement of circNUP98 in glioblastoma (GB) cancer was explored in this study. A total of 58 GB patients donated tissue samples to study circNUP98 and miR-519a (both mature and premature miRNA) expression, which was performed by RT-qPCR and heatmap analysis. The subcellular location that expresses circNUP98 was analyzed by nuclear fractionation assay. RNA pull-down assay was applied to analyze the direct interaction between circNUP98 and premature miR-519a. Overexpression assays were performed with RT-qPCR to analyze the role of circNUP98 in the expression of both mature and premature miR-519a. The role of circNUP98 and miR-519a in GB cell proliferation was analyzed by BrdU assay. Heatmap analysis showed that circNUP98 and premature miR-519a were upregulated in GB, while mature miR-519a was downregulated in GB. Across cancer tissues, circNUP98 was inversely correlated with mature miR-519a, but positively correlated with premature miR-519a. In GB cells, circNUP98 was localized to both nucleus and cytoplasm, and it directly interacted with premature miR-519a. In GB cells, circNUP98 increased premature miR-519a expression and decreased mature miR-519a expression. BrdU assay illustrated that circNUP98 overexpression reduced the inhibitory effects of miR-519a on cell proliferation. Therefore, circNUP98 suppresses the maturation of miR-519a to promote GB cell proliferation.